EFEKTIVITAS PEMUNGUTAN RETRIBUSI PASAR DI KOTA PRABUMULIH - Lisa Mandasari (ADMIN: Jurnal Administrasi Negara, 2024)
This study aims to determine and analyze the Effectiveness of Market Levy Collection in the City of Prabumulih. This research is a descriptive study with a qualitative approach. The data used is based on the type is quantitative data and qualitative data while based on the source is primary data and secondary data. Data collection instruments used were observation, interviews and documentation. The informants in this study were the Head of the Prabumulih City Regional Financial Agency; Head of UPTB Pasar Prabumulih City; Market Levy Officer Prabumulih City; and Traditional Market Traders / PTM Prabumulih City. Data analysis is a qualitative analysis with an interactive model. Based on the results of the study note that Market Levy Collection in the City of Prabumulih has not been effective because the realization of the achievement of market retribution is not in accordance with the target, where the percentage of achievements is only 57.48%. The contribution of revenue from market levies to local revenue from 2018 has increased even though the target has not been achieved.